Peran Komunikasi Orang Tua dalam Meningkatkan Kecerdasan Bahasa Anak di TK Segeran - Fatimatuz Zahra (Jurnal Pendidikan Educandum, 2025)
This article discusses the role of parental communication in improving children's language skills at Segeran Kindergarten. This research was conducted at Segeran Kindergarten in Indramayu. This research was motivated by the underdevelopment of children's intelligence at the beginning of the semester, caused by parents' inadequate motivation to engage their children in communication, thus developing language skills that can provide them with the necessary skills to continue their learning in elementary school. This study aims to describe the role of parental communication in improving children's language development. This study is a descriptive qualitative study with a field research approach. Data collection techniques used observation, interviews, and documentation. Data analysis used four stages: data reduction, data presentation, and conclusion drawing. The results indicate that (1) the role of parents in fostering communication skills in early childhood (3-6 years old) encompasses three aspects: openness, the ability to openly and express thoughts and feelings to others; empathy in good communication between parents and children; and maintaining and preserving family relationships. (2) Fostering communication skills in early childhood by parents can improve their language intelligence, which includes listening, writing, reading, and speaking.